2019
DOI: 10.33448/rsd-v8i10.1413
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Computer Assisted Language Learning (Call) to Improve English Speaking Skills

Abstract: The use of technology in learning has grown rapidly. One of them is learning English using Computer Assisted Language Learning or CALL. CALL is a computer-aided learning media used in the field of education which easy to access, spread and stored. Afterwards, this study tried to determine the influence of CALL media with lecture method and discussion to improve the cadets’ English speaking ability. This study used quantitative approach and descriptive quantitative analysis that revealed the problems occurred d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…It also entails that the students had become more confident in imitating model speakers in the courseware resulting in remarkable recognition This result conforms to the study of Ratnaningsih et al (2019) that showed a significant difference in the use of CALL media in lecture method and discussion on English speaking skill of students. This result also substantiates Mayaratri (2009) and Nachoua (2012) as cited by Ratnaningsih et al (2019), who affirmed that CALL-based learning has several advantages, such as; 1) giving a sense of fun in learning, 2) providing students the chance to be responsible in mastering the materials by doing the tasks, 3) giving students' active role in every activity during the learning process, and 4) giving students imaginative things that could be presented through computer simulations. Such circumstances can facilitate and simplify the students' minds in understanding English.…”
Section: Students' Speech Recognition Scoresupporting
confidence: 85%
“…It also entails that the students had become more confident in imitating model speakers in the courseware resulting in remarkable recognition This result conforms to the study of Ratnaningsih et al (2019) that showed a significant difference in the use of CALL media in lecture method and discussion on English speaking skill of students. This result also substantiates Mayaratri (2009) and Nachoua (2012) as cited by Ratnaningsih et al (2019), who affirmed that CALL-based learning has several advantages, such as; 1) giving a sense of fun in learning, 2) providing students the chance to be responsible in mastering the materials by doing the tasks, 3) giving students' active role in every activity during the learning process, and 4) giving students imaginative things that could be presented through computer simulations. Such circumstances can facilitate and simplify the students' minds in understanding English.…”
Section: Students' Speech Recognition Scoresupporting
confidence: 85%
“…Its users, both instructors and learners, are getting accustomed to using them to make their instructions as worldwide as possible (Ling and Donner, 2009;Xu and Peng, 2017;Li and Lan, 2022). Further, the advent and expansion of the net have made distance and open learning an opportunity for all people to receive instruction from all parts of the globe (Ratnaningsih et al, 2019). After a while, the attractiveness of distance and open instruction has supported the benefits of mobile devices to be considered as beneficial tools to realize educational purposes (Yang, 2013;Puebla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have been done on the role of technology in education in learners’ language skills and their academic achievements. Ratnaningsih et al (2019) found a significant difference in the CALL use in speaking skills. Marzban (2011) investigated the performance of EFL learners in reading comprehension using CALL and the traditional way.…”
Section: Review Of Literaturementioning
confidence: 87%